What Side Are You On? An Examination of the Persuasive Message Factors in Proposition 37 Videos on YouTube - Amber Krause; Courtney Meyers; Erica Irlbeck; Todd Chambers (Journal of Applied Communications, 2016)
California’s Proposition 37 was a ballot initiative to mandate labeling for products containing genetically modified organisms (GMOs). Although it eventually failed, it generated immense media exposure regarding GMOs and their possible regulatory, health, and economic impacts. The purpose of this study was to compare persuasive message factors in Proposition 37 videos on YouTube. A purposive sample was taken from an auto-generated YouTube channel, which resulted in 174 videos. Using content analysis, researchers identified the message position (for, against, or neutral), sources used, message frames, and message appeals. The majority of videos in the sample presented messages in support of the proposition. Citizens were the most common on-camera source. Proponent videos used more emotional appeals, while both videos against and neutral to the proposition incorporated more logical appeals. In addition, the research found three frames were used more by the videos in favor of the proposition than in videos identified as neutral or against. Overall, the results provide insight to how the videos representing for, against, and neutral message positions utilized various sources, frames, and message appeals. Recommendations for future research and practice are provided.
Keywords: Content Analysis; Framing; Genetically Modified Foods; Labeling; Persuasive Communication; YouTube